Death of a nurse [large type] - Beaton, M. C. (Beaton, M. C. Hamish Macbeth mysteries., 2016)
James Harrison has recently moved to a restored hunting lodge in Sutherland with his gorgeous private nurse Gloria Dainty. When Hamish visits Mr. Harrison to welcome him to the neighborhood, the old man treats him very rudely. Gloria apologizes for her employer's behavior, and Hamish takes the plunge and invites her out for dinner. On the appointed evening, Hamish waits for Gloria at the restaurant. And waits. Gloria never shows up. Four days later, Gloria's body washes up on the beach near Braikie. Now Hamish must find out who killed the beautiful new resident of Sutherland, and why, before the murderer strikes again